2017
DOI: 10.4236/aad.2017.62004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Social Capital and Cognitive Functions among Community-Based Elderly

Abstract: The concept of social capital encompasses all relationships and networks among people in a local community or society as a whole. It has been found to be associated with the health and daily living status of people. Furthermore, an association between social capital and cognitive functions among the elderly has been suggested in recent years. However, the number of such reports is very few. Hence, the present study aims to evaluate the relationship between social capital and cognitive functions among the elder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Lastly, consistent with previous findings from high‐income countries, we found community participation was associated with higher level of cognitive function . It is possible that by encouraging more social participation within the neighborhood, the active ingredient of “doing” could prevent cognitive decline.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lastly, consistent with previous findings from high‐income countries, we found community participation was associated with higher level of cognitive function . It is possible that by encouraging more social participation within the neighborhood, the active ingredient of “doing” could prevent cognitive decline.…”
Section: Discussionsupporting
confidence: 91%
“…Lastly, consistent with previous findings from high-income countries, we found community participation was associated with higher level of cognitive function. 6,16,19,22,23,28,39,43 It is possible that by encouraging more social participation within the neighborhood, the active ingredient of "doing" could prevent cognitive decline. Active participation in the neighborhood provides older adults with emotional support and resources for handling stressful life events.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As proposed Takechi et al (2017), it is important to prevent memory and cognitive loss with more intervention with social capital, because in research the " […] result indicates the existence of a significant correlation between social capital and cognitive functions of the elderly living in a local community", more so in Alzheimer's Syndrome.…”
Section: Application Of Educational Activities To the Elderlymentioning
confidence: 99%
“…A systematic review of studies of older people has shown a positive correlation between "social capital" and mental health [3]. The quality of "social capital", social activity, participation in decision-making in society, lack of need for care in everyday life, the depth of social relations are associated with the quality of cognitive functions of older people [4,5,6,7]. Cognitive disorders limit the ability of an aging person to participate in socio-industrial processes and require additional expenses from family members, society, social services and health care, the state for the maintenance and treatment of an elderly person [8].…”
Section: Introductionmentioning
confidence: 99%